Impact of Corporate Culture on Financial Performance:a Study on the Accepted External Commitment Values of Listed Food and Beverage Companies on The Vietnam Stock Market - Duyen Chau Thi Le; Dan Phan Van; Anh Nguyen Pham Tuyet; Thuan Tran Gia; Luan Ly Tran (PT SOLUSI EDUKASI BERDIKARI, 2025)
This study investigates the impact of external commitment values on business performance, measured by Return on Assets (ROA), for food and beverage companies in Vietnam from 2019 to 2021. Utilizing a quantitative research model, the study analyzes data from 108 annual reports of publicly listed companies on the Vietnamese stock market. The model examines seven externally validated commitment values derived from the annual reports: quality-innovation, economic, customer, people, product, social responsibility, and financial. Findings reveal that quality-innovation, people, and social responsibility values positively influence business performance, whereas economic and customer values have a negative impact.